Spectrophotometric determinations of serum phospholipids with preconcentrations of molybdophosphate-Malachite Green aggregates using a membrane filter - MATSUBARA, Chiyo; TAKAMURA, Kiyoko; YONEHARA, Yoshiyuki; YOSHIHARA, Kazuhiro; KOBAYASHI, Narumi (BUNSEKI KAGAKU, 1989)
High sensitive spectrophotometric determinations of serum phospholipids were conducted. The levels of serum phospholipids reflect liver functions, so thier determinations are clinically important. Phospholipids are hydrolyzed by phospholipase C and alkakine phosphatase with the release of phosphate. The resulting phosphate associated with Mo-MG reagent (mixed solution of ammonium molybdate and Malachite Green) to form molybdophosphate-Malachite Green aggregates. The aggregates were selectively collected on a nitro cellulose membrane filter (pore size:3.0 μm) and dissolved in methylcellosolve along with the membrane filter. Absorbance (λ: 627 nm) was proportional to the amount of phospholipids. Molar absorptivity of the aggregates in methylcellosolve (ε=2.8 × 105 M-1 cm-1) was large enough to minimize the serum sample for determination. Ascorbic acid, bilirubin, Na+, K+, Ca2+ and Cl- in serum did not affect the results obtained by this method.